2015
DOI: 10.2217/fon.15.15
|View full text |Cite
|
Sign up to set email alerts
|

Common EGFR -Mutated Subgroups (Del19/L858R) in Advanced Non-Small-Cell Lung Cancer: Chasing Better Outcomes with Tyrosine Kinase Inhibitors

Abstract: Ten years ago, somatic mutations in EGFR were identified in patients with non-small-cell lung cancer. Demonstration of the antitumor efficacy of EGF receptor-directed tyrosine kinase inhibitors resulted in their approval for the treatment of advanced non-small-cell lung cancer. Insights into the role of EGFR-sensitizing mutations and acquired and de novo T790M resistance mutations followed, and differences in progression-free survival for patients with EGFR Del19- and L858R-mutated tumors treated with reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 67 publications
5
54
0
5
Order By: Relevance
“…Approximately 30%–50% of Asian and 10%–17% of Caucasian patients with lung adenocarcinoma harbor activating epidermal growth factor receptor ( EGFR ) mutations 1,2. EGFR-tyrosine kinase inhibitors (TKIs) such as gefitinib and erlotinib are the preferred treatment for patients with activating EGFR mutations (a deletion in exon 19 [19del] and a point mutation in exon 21 leading to substitution of leucine for arginine at position 858 [L858R]).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30%–50% of Asian and 10%–17% of Caucasian patients with lung adenocarcinoma harbor activating epidermal growth factor receptor ( EGFR ) mutations 1,2. EGFR-tyrosine kinase inhibitors (TKIs) such as gefitinib and erlotinib are the preferred treatment for patients with activating EGFR mutations (a deletion in exon 19 [19del] and a point mutation in exon 21 leading to substitution of leucine for arginine at position 858 [L858R]).…”
Section: Introductionmentioning
confidence: 99%
“…Both vary in their activated stability by difference in conformation, and their continuation state of kinase activation after the disruption of dimerization is different also [21]. Reguart et al reported that biological properties of Del19 and L858R mutations differ, with different patterns of EGFR amplification and EGFR autophosphorylation between cell lines containing each mutation [22]. Other experimental reports show that [26].…”
Section: Discussionmentioning
confidence: 99%
“…Somatic EGFR mutations are present in around 50% of patients in Asia and in 10–15% of Caucasian patients with metastatic NSCLC with adenocarcinoma histology (7). Most of these mutations are caused by deletions on the exon 19 or L858R point mutations on exon 21 (8). EGFR-activating mutations lead to aberrant constitutive signaling by EGFR and its associated cell signaling pathways.…”
Section: Introductionmentioning
confidence: 99%